If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3y)(x + -3y) = 0 Multiply (2x + -3y) * (x + -3y) (2x * (x + -3y) + -3y * (x + -3y)) = 0 ((x * 2x + -3y * 2x) + -3y * (x + -3y)) = 0 Reorder the terms: ((-6xy + 2x2) + -3y * (x + -3y)) = 0 ((-6xy + 2x2) + -3y * (x + -3y)) = 0 (-6xy + 2x2 + (x * -3y + -3y * -3y)) = 0 (-6xy + 2x2 + (-3xy + 9y2)) = 0 Reorder the terms: (-6xy + -3xy + 2x2 + 9y2) = 0 Combine like terms: -6xy + -3xy = -9xy (-9xy + 2x2 + 9y2) = 0 Solving -9xy + 2x2 + 9y2 = 0 Solving for variable 'x'. Factor a trinomial. (x + -3y)(2x + -3y) = 0Subproblem 1
Set the factor '(x + -3y)' equal to zero and attempt to solve: Simplifying x + -3y = 0 Solving x + -3y = 0 Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 x + 0 = 0 + 3y x = 0 + 3y Remove the zero: x = 3y Simplifying x = 3ySubproblem 2
Set the factor '(2x + -3y)' equal to zero and attempt to solve: Simplifying 2x + -3y = 0 Solving 2x + -3y = 0 Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 2x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 2x + 0 = 0 + 3y 2x = 0 + 3y Remove the zero: 2x = 3y Divide each side by '2'. x = 1.5y Simplifying x = 1.5ySolution
x = {3y, 1.5y}
| 250=14x+22x | | 4x-10+2x=62 | | 3(s+22)=4(s+2) | | 3(1-r)+5r=4(r+1)+5 | | 5+x+-3x=3x-2x-1 | | 3.4t+0.008=11 | | -x-30=3x+6 | | 45=3V | | -4r+5=2(2.5-2r) | | M^2+6m-16= | | 14-3(5t+-12)=1-(20t+1) | | 6z-4=9z+14 | | 8x+16=22+8x | | -33=r+(-26) | | (-5)+(9)= | | 14xy-7x^2+5x=0 | | x^2+10x+17=y | | (4x-2y)+70=180 | | 67=13+u | | 25c=675 | | (3m+6n)(7m+2n)= | | X+(x-10)=90 | | -8*+30=10 | | X^2+3x=13 | | x^2+10x+23=y | | 57+4=s | | x^2+34x+c=0 | | 0=(-16t^2)+30t+3 | | 4x-5x+15=-4+3x+3 | | 3(y-1)-7=-2(-8y+3)-7y | | 6k-8k-9k=7 | | 8x+2-10= |